The Role of Regional Government Information System (SIPD) on the Sub-District of Aertembaga’s Financial Accountability - Alfred Salindeho (International Journal Labs, 2021)
This study aims to analyze the benefits of using the Local Government Information System (SIPD) on financial accountability in the Regional Government of Aertembaga District. The research method used is a qualitative research method with an exploratory approach. Data were obtained through field observations, interviews with key informants and documentation studies. Key informants were interviewed with certain considerations and objectives. Triangulation technique was used to test the validity of the data and data sources. The transcript data described from the interviews were analyzed using analytical methods consisting of giving themes/coding, conceptualizing scientific statements and interpreting them in narrative form. The results showed that the benefits of using SIPD on financial accountability in the Aertembaga District Government made inputting budget plans timely, relevant and easy to do.